TTB Protects Astrocytes Against Oxygen-Glucose Deprivation/Reoxygenation-Induced Injury via Activation of Nrf2/HO-1 Signaling Pathway - Liu, Liang; Zhao, Zhichen; Yin, Qimeng; Zhang, Xiaolu (Frontiers in Pharmacology, 2019)
Neonatal hypoxia/ischemic encephalopathy (NHIE) is a severe condition that occurs death or neurological disability in newborns. The underlying pathological mechanisms are unclear and developing the target neuroprotective strategies are urgent. 2,7,2'-trihydroxy-4,4',7'-trimethoxy-1,1'-biphenanthrene (TTB) is a natural product isolated from Cremastra appendiculata (D. Don) Makino and Liparis nervosa (Thunb.) Lindl. TTB has demonstrated potent cytotoxic activity against stomach (HGC-27) and colon (HT-29) cancer cell lines. However, none of studies have addressed the effects of TTB in NHIE. In the present study, an oxygen-glucose deprivation/ reoxygenation (OGD/R)-induced astrocytes injury model was established to investigate the effect of TTB and its potential mechanisms. Our results showed that TTB alleviated the OGD/R-induced reactive oxygen species (ROS) increase and the intracellular antioxidant capacity of superoxide dismutase (SOD) activity decrease. Moreover, TTB potentially prolonged activation state of nuclear factor erythroid-2 related factor 2(Nrf2)/heme oxygenase-1(HO-1) pathway and maintained the protection against oxidative stress in OGD/R-induced astrocytes by inducing the nuclear translocation and the upregulation of Nrf2, along with enhanced expression of downstream target gene HO-1. Furthermore, TTB treatment diminished the accumulation of hypoxia induced factor 1α (HIF1α) and vascular endothelial growth factor (VEGF) expression induced by OGD/R. We also found TTB-treated astrocytes reversed the inhibition of OGD/R on neurites growth of neurons by astrocyte-neuron co-culture system. In conclusion, TTB inhibited OGD/R-induced astrocytes oxidative stress, at least partially through inhibition of HIF1α and VEGF via Nrf2/HO-1 signaling pathway.